Simultaneous Micro-Structuring and Surface Smoothing of Additive Manufactured Parts Using DLIP Technique and Its Influence on the Wetting Behaviour - Kuisat, Florian; Ränke, Fabian; Lasagni, Fernando; Lasagni, Andrés Fabián (Materials, 2021)
It is well known that the surface topography of a part can affect its function as well as its mechanical performance. In this context, we report on the surface modification of additive manufactured components made of Titanium 64 and Scalmalloy®, using Direct Laser Interference Patterning technique. In our experiments, a nanosecond-pulsed near-infrared laser source with a pulse duration of 10 ns was used. By varying the process parameters, periodic structures with different depths and associated roughness values are produced. Additionally, the influence of the resultant morphological characteristics on the wettability behaviour of the fabricated textures is investigated by means of contact angle measurements. The results demonstrated a reduction of the surface roughness of the additive manufactured parts (in the order of some tens of micrometres) and simultaneously the production of well-defined micro-patterns (in the micrometre range), which allow the wettability of the surfaces from 26° and 16° up to 93° and 131° to be tuned for Titanium 6Al 4V and Al-Mg-Sc (Scalmalloy®), respectively.